D’une rive l’autre : questions de génétique et poétique - Nicolas Martin-Granel (Continents manuscrits)
In this article, we will ask to what extent a genetic approach, which postulates that “text doesn’t exist”, implying the necessity of going upstream, to before the text is printed, wouldn’t actually go against this literature of the Congo River which, on the contrary, postulates, through the image of a continuous, dynamic, and irreversible flux which “defenestrates itself in the Ocean”, that the draft or the “avant-text” does not need be. In fact, through serendipitous encounters with texts, terrains, and artists of both shores of the Congo, we realize that this inextricable tension between the poetic katabasis and genetic anabasis over-determines the undisciplined and multiforme “river-like” dynamic carried through all artistic practices, from writing to the visual arts, living or performance art, and this, according to the global model of “l’Art salvateur” with no origin and no end.